DBS in Treatment of Post-Traumatic Stress Disorder - Angelo Lavano; Giusy Guzzi; Attilio Della Torre; Serena Marianna Lavano; Raffaele Tiriolo; Giorgio Volpentesta (Brain Sciences, 2018)
Post-traumatic stress disorder (PTSD) is a debilitating psychiatric condition for which pharmacological therapy is not always solvable. Various treatments have been suggested and deep brain stimulation (DBS) is currently under investigation for patients affected by PTSD. We review the neurocircuitry and up-to-date clinical concepts which are behind the use of DBS in posttraumatic stress disorder (PTSD). The role of DBS in treatment-refractory PTSD patients has been investigated relying on both preclinical and clinical studies. DBS for PTSD is in its preliminary phases and likely to provide hope for patients with medical refractory PTSD following the results of randomized controlled studies.